Prevalence of Trichomonas vaginalis Among Women in the Chinese Population: A Systematic Review and Meta-Analysis - Shuang Li; Jiahui Xu; Sisi Ru; Changjun Hu; Chongyang Liu; Xingquan Sun; Heteng Guo; Xi Zhang (Tropical Medicine and Infectious Disease)
Trichomonas vaginalis (TV) is the most common non-viral sexually transmitted infection (STI) among women worldwide. However, there is little information available regarding the burden of trichomoniasis infection among Chinese women. The aim of the present study is to assess the status of trichomoniasis in China. To address this gap, we searched seven databases for relevant studies published from their inception to June 2024. The overall prevalence of T. vaginalis in China was determined to be 6.31% with a high level of heterogeneity (I2 = 99.68%). Subgroup analysis also demonstrated a statistically significant association between the T. vaginalis prevalence in the type of population, age range, year, residential status, and province. Among these, sex workers are the most prominent with 12.16%. Meta-regression analysis indicated that the infection rate of T. vaginalis among Chinese women had not shown a significant decline over time (p = 0.2919). Therefore, it continues to be a public health issue that should not be overlooked. Sex workers and rural women have a relatively higher infection rate of trichomoniasis, and this is largely associated with sexual safety awareness and hygiene conditions. Our findings provide crucial information for healthcare authorities and can shed light on the prevention strategies for trichomoniasis in China.